Implementation of Sustainable Practices Based on Ecovadis Recommendations In Flavor and Fragrance Raw Material Supply Companies - Muhammad Sohibullah; Gouvana Febriani Talapessy (International Journal Labs, 2025)
This research aims to evaluate the sustainability performance of PT XYZ, a company in the flavor & fragrance industry, during the year 2023 by the EcoVadis platform. Data was collected from the company's policy documents, external audits, and sustainability reports, employing a qualitative research methodology for analysis and evaluation. The sustainability performance assessment of PT XYZ was conducted using an external approach, utilizing the EcoVadis platform. EcoVadis provides a dynamic assessment of a company's sustainability performance in four main themes: Environment, Labor & Human Rights, Ethics, and Sustainable Procurement. The assessment results indicate that PT XYZ achieved a silver medal with an overall score of 68, which is among the top 15%. The company has strong policies in place regarding environmental, human rights, ethical, and sustainable procurement practices. External audits confirmed the company's compliance with these policies. Additionally, the company has shown a strong commitment to mitigating environmental impacts, supporting human rights, conducting ethical business practices, and integrating sustainability into its supply chain. The sustainability performance assessment of PT XYZ in 2023 holds significant value in depicting the company's commitment to sustainable business practices in the flavor & fragrance industry. The results provide a clear picture of the extent to which PT XYZ complies with global sustainability standards and how the company performs in environmental, social, and ethical aspects. This research also highlights the importance of platforms like EcoVadis in helping companies communicate their sustainability performance to customers and other stakeholders.